(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The main emphasis of this research was to describe air pollution level and dispersion in a typical street canyon (Valdemara Street in Riga (Latvia) city centre), afterward to postulate potential development scenarios and perform modelling in order to understand the influence on air pollution level. For this purpose special mathematical model was used - Operational Street Pollution Model (OSPM), which was developed by the National Environmental Research Institute in Denmark. Following development scenarios were tested: (1) realistic environmentally friendly - decrease of traffic flow by 50 %, as according to street interviews about 36 - 50 % of drivers are ready to change driving habits from car to bicycle; (2) strictly limited – “green light” for public transport, but restrictions for old private cars, flow speed limitations.